2019
DOI: 10.1002/mus.26433
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA‐92a increases blood vessels and satellite cells in skeletal muscle but does not improve duchenne muscular dystrophy–related phenotype in mdx mice

Abstract: Introduction: The vasculature and blood flow in muscle are perturbed in Duchenne muscular dystrophy (DMD) and its mdx mouse model. MicroRNA‐92a (miR‐92a) is enriched in endothelial cells, especially during ischemic injury. Methods: Because antagonizing miR‐92a was shown to result in increased proliferation and migration of endothelial cells and recovery from ischemia, we assessed the effects of Antagomir‐92a in vitro in muscle stem cell culture and in vivo in mdx mice. Results: miR‐92a was found to be highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…family is a central epigenetic regulators that showed to have a significant role as anti-tumorigenic molecules in different forms of cancer (Iqbal et al, 2012;Tari et al, 2018). Additionally, miR-92a plays a crucial role in the growth of human organs such as heart (Wong et al, 2016), lungs (Zhu et al, 2018) and immune system (Liang et al, 2016) but also the formation of blood vessels (Verma et al, 2019). The circulating levels of mir-92a was found to be elevated in the liver tissue of patients with hepatocellular carcinoma (Shigoka et al, 2010), while low levels of mir-92a were correlated with multiple myeloma (Yoshizawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…family is a central epigenetic regulators that showed to have a significant role as anti-tumorigenic molecules in different forms of cancer (Iqbal et al, 2012;Tari et al, 2018). Additionally, miR-92a plays a crucial role in the growth of human organs such as heart (Wong et al, 2016), lungs (Zhu et al, 2018) and immune system (Liang et al, 2016) but also the formation of blood vessels (Verma et al, 2019). The circulating levels of mir-92a was found to be elevated in the liver tissue of patients with hepatocellular carcinoma (Shigoka et al, 2010), while low levels of mir-92a were correlated with multiple myeloma (Yoshizawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we have found that miR-146a, known to diminish inflammation and fibrosis in different tissues by downregulating the expression of proinflammatory cytokines, does not significantly affect the deleterious pathological events of DMD progression in mdx mice [ 224 ]. Another study pointed out the lack of beneficial effect of miR-92a inhibition on DMD progression in mdx mice despite the increased capillary density and tissue perfusion that was found after antagomir-92a [ 270 ].…”
Section: New Modulators Of Dmd Progressionmentioning
confidence: 99%
“…Skeletal muscles are consolidated tissue and consist of aligned multinucleated myocytes, satellite cells, nerves, blood vessels, and extracellular matrix (ECM) in complex structures [ 1 3 ]. Like other tissues, skeletal muscles are sensitive to varied acute and chronic injuries caused by physical trauma, plastic/cosmetic surgeries, arterial occlusion, metabolic diseases, peripheral nerve atrophies, congenital diseases, etc.…”
Section: Introductionmentioning
confidence: 99%